Impact of Cooling Methods on the Valorisation of Calcined Dam Sediments in Self-Compacting Concrete - Ahmed Sweiti; Rabah Chaid; El-Hadj Kadri (Salehan Institute of Higher Education, 2026)
Dam sedimentation poses critical environmental and operational challenges worldwide, requiring sustainable valorisation strategies. This study investigates how post-calcination cooling protocols influence the pozzolanic performance of Ksob dam sediments (Algeria) as a partial cement replacement in self-compacting concrete (SCC). Raw sediments were calcined at 750 °C for 5 h and subjected to three cooling methods: water quenching (WQCS), air cooling (ACCS), and slow furnace cooling (SCCS). Ten SCC formulations were prepared with 10%, 15%, and 20% cement substitution rates. Despite the reduced binder content, all mixtures maintained self-compacting properties (spread: 700-735 mm; T₅₀₀: 1.06-1.39 s) with moderate superplasticiser adjustment, up to 1.2% of binder mass. WQCS formulations exhibited superior performance: at 10% substitution, compressive strength reached 97% of the control at 180 days, while water absorption and permeable porosity decreased relative to the control by 7.1% and 1.9%, respectively. TGA/DSC analysis attributed these gains to enhanced pozzolanic C-S-H formation. These findings demonstrate that cooling kinetics critically govern the mineralogical transformation and reactivity of calcined sediments. Water quenching proved optimal for producing high-performance, eco-efficient SCC, offering a viable pathway for large-scale dam sediment valorisation while lowering the cement industry’s carbon footprint.